Five new earthworm species of the Pheretima sangirensis-group (Clitellata: Megascolecidae) from Mount Banahaw, Quezon Province, Philippines - Hong, Yong; James, Samuel W. (Zootaxa, 2026)
Five new species of the genus Pheretima are described from Mount Banahaw, Quezon Province, Luzon I., Philippines: P. banahawensis sp. nov., P. sancta sp. nov., P. taceae sp. nov., P. apolinarioi sp. nov., and P. madii sp. nov. All five species belong to the sangirensis–group as defined by Sims and Easton (1972), characterized by one pair of spermathecal pores located on intersegmental furrow 7/8. Pheretima banahawensis sp. nov. has spermathecal pores spaced 2–2.5 mm apart and copulatory bursae openings spaced 0.09–0.13 of the body circumference apart. Pheretima sancta sp. nov. shows spermathecal pore spacing of 1.9–2.1 mm and copulatory bursae openings 0.14–0.18 circumference apart. Pheretima taceae sp. nov. has spermathecal pores 1.4 mm apart and copulatory bursae openings 0.13 circumference apart. Pheretima apolinarioi sp. nov. exhibits spermathecal pore spacing of 1–1.1 mm and copulatory bursae openings 0.12–0.13 circumference apart. Pheretima madii sp. nov. presents the shortest distances, with spermathecal pores 0.4–0.6 mm apart and copulatory bursae openings 0.10–0.13 circumference apart. Detailed descriptions of these new species, including illustrations of the ventral view and representative spermathecae, are provided.